'Microbial mortar'-restoration of degraded marble structures with microbially induced carbonate precipitation. (20th August 2018) - Minto, James M.; Tan, Qian; Lunn, Rebecca J.; El Mountassir, Gráinne; Guo, Hongxian; Cheng, Xiaohui
Highlights: Microbial mortar can successfully restore degraded marble. Reagent transport evolved with each treatment cycle. Micro-continuum flow simulation of 3D X-ray data revealed changing flow paths. Abstract: To evaluate a restoration strategy for highly degraded marble structures, microbially induced carbonate precipitation (MICP) has been employed to reduce porosity and permeability in a column filled with coarse crushed marble. A 3D X-ray tomography scan revealed the spatial variation in porosity throughout the column and tracer breakthrough curves, recorded at intervals during treatment, enabled derivation of core-scale fluid transport properties and their alteration by precipitating carbonate. Micro-continuum scale flow modelling based on the X-ray data indicated that treatment led to changes in the pore network structure with flow increasingly focused into a smaller number of faster flowing open channels.